Acanthamoeba polyphaga Strain Age and Method of Cyst Production Influence the Observed Efficacy of Therapeutic Agents and Contact Lens Disinfectants - Hughes, Reanne (American Society for Microbiology, 2003)
The effects of age in culture and the type of medium used for induction of Acanthamoeba polyphaga (Ros) cysts on susceptibilities to polyhexamethylene biguanide (PHMB; 3 μg/ml), chlorhexidine digluconate (30 μg/ml), myristamidopropyl dimethylamine (20 μg/ml), H(2)O(2) (3%), and two multipurpose contact lens solutions (MPS-1 and MPS-2, based on 1 μg of PHMB per ml) were examined. Strain Ros-02 was cryopreserved on isolation in 1991, while strain Ros-91 had been in continuous axenic culture. Significant differences in susceptibilities to the disinfectants were found depending on the medium used for cyst preparation and the age of the test strain, with Ros-02 generally being more resistant. For example, the killing of Ros-91 cysts produced from an axenic culture of trophozoites in the presence of 50 mM MgCl(2) by MPS-2 was 4 logs, but the killing of Ros-02 by MPS-2 was only 2 logs (P < 0.05) and killing of both strains with cysts obtained from monoxenic cultures with Escherichia coli was only 1 log (P < 0.001). Assays repeated with different batches of the various cyst types gave consistent results. A batch of Ros-91 cysts stored at 4°C and tested over an 8-week period with MPS-1 showed progressively increasing susceptibility to disinfection, although there was no loss of viability during storage (P < 0.01). These observations have important implications for the standardization and interpretation of Acanthamoeba disinfectant and therapeutic agent testing.